SIMULASI PENGUKURAN LONGSOR PADA KEMIRINGAN LERENG DAN KETEBALAN SERESAH YANG BERBEDA - Muhamad Afif Akbar; Sri Rahayu Utami; Christanti Agustina (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Most areas in Indonesia have a high risk of landslides due to geological and geographical conditions. Landslide is affected by natural factors (such as slope stability) and human-made factors (such as land use). Slope stability is influenced by morphological conditions and hydrological conditions. Land use or land cover may affect surface roughness, which determines the infiltration rate into the soil. This study was an attempt to explore the influence of slope gradient and litter thickness on time required for landslides and the volume of landslides. This research was carried out in two different locations, Agro Techno Park and the Experimental Garden of the Faculty of Agriculture. The study was conducted in eight treatments, combinations of three factors, i.e. soil texture, slope gradient, and litter thickness, using ten replications. The duration required for landslides and the volume of landslides were measured. The gradient of the slope has a significant effect on the volume of landslides. An increase in slope at any litter thickness resulted in up to three times more volume. The difference in slope also has a significant effect on the time required for landslides. The clayey texture needs two times the longer time required for landslides to occur. The slope gradient has a more dominant influence than the thickness of litter and soil texture. The effect of the thickness of the litter is getting bigger; on the other hand, the effect of soil texture is getting smaller with increasing slope.